Penerapan Data Mining Dalam Meningkatkan Mutu Perawatan dan Perbaikan Perlengkapan Alat-Alat Kapal Laut Menerapkan Metode K-Means Clustering - Yulifa Esfana Putri Sinaga; Garuda Ginting; Melda Panjaitan (Universitas Budi Darma, 2021)
This study aims to propose in carrying out sailing activities on the KN. Arcturus ship every week, so that maintenance and maintenance activities need to be carried out properly and scheduled so as not to interfere with ongoing production activities. The current machine breakdown is still relatively high and requires a long repair time, what is proposed is preventive maintenance using the Clustering technique. The method used is K-Means Clustering. By using this method, the data that has been obtained can be grouped into several clusters, based on the similarity of these data, so that data that has the same characteristics are grouped into one cluster and those that have different characteristics are grouped into another cluster. We can use the abundance of data to find hidden information from these data. In order to find out the hidden information from these data, it is necessary to process the data. The data processing process is also known as data mining. With this grouping it will know the results of the analyzed data.